POTENSI BATIK SEBAGAI DAYA TARIK DESA WISATA (Studi di Kecamatan Bayat Kabupaten Klaten Propinsi Jawa Tengah) - Krestanto, Hery (Sekolah Tinggi Pariwisata AMPTA, 2018)
This study aims to determine the potential of batik as an attraction for tourist villages. This research was conducted in the needle village of Bayat sub-district, Klaten district, Central Java province. Types of data collected in this study are qualitative data, namely the potential of batik as an attraction for tourist villages in the needle village of Bayat district, Klaten district, Central Java province. Data collection techniques used are interviews, observation, documentation. The results of this study are the potential of batik as an attraction for tourist villages in the needle village of Bayat district, Klaten district, Central Java, the potential of batik produced include canting batik, paid batik motifs, wooden batik. Keywords: Batik Potential, Attraction, Tourism Village